Advocate Illinois Masonic Medical Center, Chicago, IL Community Health Needs Assessment: The Need for Resident Physician Engagement - Antoine, Ranae (Ochsner J, 2018)
BACKGROUND: The Patient Protection and Affordable Care Act of 2010 requires tax-exempt hospitals to conduct a CHNA every 3 years. Since Advocate Illinois Masonic Medical Center began conducting CHNAs, residents have not been part of the Health Council charged with designing and executing the assessment. Only one residency program in the country has been actively involved in its hospital’s CHNA process, and the outcome was documented as extremely positive. We included a resident physician in the hospital CHNA process to provide a resident’s perspective on community needs and interventions to address those needs. METHODS: An internal medicine resident was assigned to Advocate Illinois Masonic’s Community Health Council. A mini-CHNA was conducted with the internal medicine residents to mirror the wider CHNA process. The top community needs identified by the residents were compared to the needs identified by the council. RESULTS: The council priorities matched the resident priorities: chronic diseases, behavioral health/substance abuse, and social determinants of health. The greatest barriers to healthcare identified by the residents were lower socioeconomic status (34%) and lack of education (33%). Eighty-two percent of the internal medicine residents had no prior knowledge of the CHNA concept, 35% reported that they do not have adequate knowledge of community resources, and 84% said they would participate in a CHNA if given the opportunity. The resident on the Health Council reported enhanced knowledge of community resources and increased comfort with discussing healthcare barriers in the community. CONCLUSION: Improved communication and education about community resources will improve resident physicians’ ability to care for patients. Resident physicians’ perspectives of health need priorities are enhanced through front-line experience. Including a resident on the Health Council greatly benefited both parties.